THE EFFECT OF USING BIG BOOK MEDIA ON LEARNING INTEREST AND LEARNING RESULTS OF SOCIAL SCIENCE - Lisa Bela; Nursalam; Idawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the use of Big Book media toward students' interest and learning outcomes in social science. This research used a quantitative approach and quasi-experimental research type. The data collection techniques used were: questionnaires, tests, and documentation. The Kolmogorov-Smirnov test and the Homogeneity of Variances test were operated to answer the formulation of the problem, and finally T-test was operated to test the hypothesis that has been proposed. The results of this study were: (1) there was a significant influence between Big Book media on social studies interests as evidenced by the tcount> t table (7,656> 2,0003) and the t significance value for the questionnaire variable was 0,000; this value was smaller than the probability 0.05 (0.000 <0.05); (2) there was a significant influence between Big Book media on social studies learning outcomes as evidenced by the value of tcount> t-table (3.982> 2.0003) for the T-test variable. The significance value of t for the test variable was equal to 0.000 and this value was smaller than the probability of 0.05 (0.000 <0.05); and (3) there was a significant influence between Big Book media on the social studies learning interest and learning outcomes as evidenced by the value of tcount> ttable (7,656> 2,0003) for the questionnaire variable, while for the test variable (3,982> 2,0003). The significance value of t for the questionnaire and test variables was both 0,000 and this value was is smaller than the probability of 0.05 (0,000 <0.05)